Knowledge Science, Engineering and Management 4th International Conference, KSEM 2010, Belfast, Northern Ireland, UK, September 1-3, 2010. Proceedings - Bi, Yaxin; Williams, Mary-Anne.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 4th International Conference on Knowledge Science, Engineering and Management held in Belfast, Northern Ireland, UK, in September 2010.
Mining Video Data: Learning about Activities -- Ontology Languages and Engineering -- Theory of Belief Functions for Data Analysis and Machine Learning Applications: Review and Prospects -- Modeling Ontological Concepts of Locations with a Heterogeneous Cardinal Direction Model -- Finding Minimal Rare Itemsets and Rare Association Rules -- Background Knowledge Integration in Clustering Using Purity Indexes -- A Comparison of Merging Operators in Possibilistic Logic -- Modelling and Reasoning in Metamodelling Enabled Ontologies -- Towards Encoding Background Knowledge with Temporal Extent into Neural Networks -- A Fuzzy Description Logic with Automatic Object Membership Measurement -- Decomposition-Based Optimization for Debugging of Inconsistent OWL DL Ontologies -- A Concept Hierarchy Based Ontology Mapping Approach -- Composing Cardinal Direction Relations Basing on Interval Algebra -- Retrieval Result Presentation and Evaluation -- Autonomy: Life and Being -- A Method of Social Collaboration and Knowledge Sharing Acceleration for e-Learning System: The Distance Learning Network Scenario -- A Comparative Study of Target-Based Evaluation of Traditional Craft Patterns Using Kansei Data -- Optimization of Multiple Related Negotiation through Multi-Negotiation Network -- Reasoning Activity for Smart Homes Using a Lattice-Based Evidential Structure -- Knowledge Modelling to Support Inquiry Learning Tasks -- Building the Knowledge Base to Support the Automatic Animation Generation of Chinese Traditional Architecture -- Discovery of Relation Axioms from the Web -- An Improved Piecewise Aggregate Approximation Based on Statistical Features for Time Series Mining -- Incorporating Duration Information in Activity Recognition -- A Graphical Model for Risk Analysis and Management -- Towards Awareness Services Usage Characterization: Clustering Sessions in a Knowledge Building Environment -- Adjusting Class Association Rules from Global and Local Perspectives Based on Evolutionary Computation -- Probabilistic Declarative Process Mining -- Making Ontology-Based Knowledge and Decision Trees Interact: An Approach to Enrich Knowledge and Increase Expert Confidence in Data-Driven Models -- A Novel Initialization Method for Semi-supervised Clustering -- Constructing and Mapping Fuzzy Thematic Clusters to Higher Ranks in a Taxonomy -- Anticipation as a Strategy: A Design Paradigm for Robotics -- Modular Logic Programming for Web Data, Inheritance and Agents -- Automatic Collecting Technique of Low Frequency Electromagnetic Signals and Its Application in Earthquake Study -- Improving Search in Tag-Based Systems with Automatically Extracted Keywords -- Towards a Framework for Trusting the Automated Learning of Social Ontologies -- PlayPhysics: An Emotional Games Learning Environment for Teaching Physics -- A SOM-Based Technique for a User-Centric Content Extraction and Classification of Web 2.0 with a Special Consideration of Security Aspects -- Modularizing Spatial Ontologies for Assisted Living Systems -- Towards Scalable Instance Retrieval over Ontologies -- MindDigger: Feature Identification and Opinion Association for Chinese Movie Reviews -- The Impact of Latency on Online Classification Learning with Concept Drift -- Efficient Reasoning with RCC-3D -- Automated Ontology Generation Using Spatial Reasoning -- Facilitating Experience Reuse: Towards a Task-Based Approach -- Behavioural Rule Discovery from Swarm Systems -- Knowledge Discovery Using Bayesian Network Framework for Intelligent Telecommunication Network Management -- Combining Logic and Probabilities for Discovering Mappings between Taxonomies -- An Ontology-Based Semantic Web Service Space Organization and Management Model -- Genetic Algorithm-Based Multi-objective Optimisation for QoS-Aware Web Services Composition -- Knowledge Merging under Multiple Attributes -- Feature Selection Based on Mutual Information and Its Application in Hyperspectral Image Classification -- Static, Dynamic and Semantic Dimensions: Towards a Multidisciplinary Approach of Social Networks Analysis -- Knowledge Based Systems and Metacognition in Radar -- Maximus-AI: Using Elman Neural Networks for Implementing a SLMR Trading Strategy -- A Formalism for Causal Explanations with an Answer Set Programming Translation -- Earthquake Prediction Based on Levenberg-Marquardt Algorithm Constrained Back-Propagation Neural Network Using DEMETER Data -- Affinity Propagation on Identifying Communities in Social and Biological Networks -- Semantic Decomposition of Indicators and Corresponding Measurement Units -- Engineering Knowledge for Assistive Living -- Large-Scale, Exhaustive Lattice-Based Structural Auditing of SNOMED CT.
Keywords: Computer science; Information systems; Database management; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer Science; Data Mining and Knowledge Discovery; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Database Management; Information Systems and Communication Service